TRIM21-mediated METTL3 degradation promotes PDAC ferroptosis and enhances the efficacy of Anti-PD-1 immunotherapy - Wenhao Mao; Qian Jiang; Yadan Feng; Chen Peng; Hui Peng; Xuan Li; Lin Jiao; Li Zhang; Liwei Ma; Ting Sun (Cell Death and Disease)
Abstract Pancreatic cancer remains the most lethal human malignancy with limited clinical benefits from currently available anticancer treatments. Ferroptosis has recently attracted great attention as a potential antineoplastic strategy. However, the study of ferroptosis in PDAC remains insufficient. This study revealed that Methyltransferase like 3 (METTL3), as a key oncogenic factor, is frequently upregulated and inhibits ferroptosis by stabilizing SLC7A11 mRNA in PDAC. In addition, we identified a novel post-translational modification of METTL3 and characterized specific regulatory mechanisms of METTL3 protein degradation. The E3 ligase TRIM21 mediated K48-linked polyubiquitination of METTL3 at the K459 site, leading to the proteasomal degradation of METTL3, which prevented tumor progression by promoting ferroptosis. Interestingly, the TRIM21-METTL3 axics mediated ferroptosis effectively increased the expression of immune checkpoint PD-L1 and strengthened antitumor immunity in pancreatic cancer. Together, our findings first elucidated the detailed molecular mechanism of METTL3 degradation and revealed the pivotal role of the TRIM21-METTL3 axis in regulating ferroptosis and antitumor immunity, which may serve as a potential target for pancreatic cancer treatment.